2024
DOI: 10.3847/1538-4357/ad1a15
|View full text |Cite
|
Sign up to set email alerts
|

An Excess of Active Galactic Nuclei Triggered by Galaxy Mergers in MaNGA Galaxies of Stellar Mass ∼1011 M

Julia M. Comerford,
Rebecca Nevin,
James Negus
et al.

Abstract: To facilitate new studies of galaxy-merger-driven fueling of active galactic nuclei (AGNs), we present a catalog of 387 AGNs that we have identified in the final population of over 10,000 z < 0.15 galaxies observed by the Sloan Digital Sky Survey-IV (SDSS-IV) integral field spectroscopy survey Mapping Nearby Galaxies at Apache Point Observatory (MaNGA). We selected the AGNs via mid-infrared Wide-field Infrared Survey Explorer colors, Swift/Burst Alert Telescope ultra-hard X-ray detections, NRAO Very Large A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 93 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…However, observationally, the connection between galaxy mergers and SMBH activity remains poorly understood; various studies have found conflicting results regarding whether mergers are responsible for, or even correlated with, SMBH activity [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. The activity of AGNs is likely obscuration-and merger-stage-dependent [42,52,53].…”
Section: Detecting Dual Agnsmentioning
confidence: 99%
“…However, observationally, the connection between galaxy mergers and SMBH activity remains poorly understood; various studies have found conflicting results regarding whether mergers are responsible for, or even correlated with, SMBH activity [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. The activity of AGNs is likely obscuration-and merger-stage-dependent [42,52,53].…”
Section: Detecting Dual Agnsmentioning
confidence: 99%